Timeshare industry leadership and human resource implications of employee and guest satisfaction - Maier, Thomas A.; Gursoy, Dogan (London : International CHRIE, 2013)
Kalalau Timeshare/Vacation Ownership Inc. was founded in 2001 and currently owns, operates and manages 30 resorts across 8 states in the US. At the annual strategic conference the CEO of Kalalau Timeshare/Vacation Ownership Inc. wants a closer examination of a few key factors associated with company performance; employee satisfaction, customer satisfaction and facilities maintenance. Students are asked to examine the data on employment and staff satisfaction and make strategic recommendations for how Kalalau Inc. should proceed.
Originally published in : Maier, T. A., & Gursoy, D. (2013). Timeshare industry leadership and human resource implications of employee and guest satisfaction. Journal of Hospitality & Tourism Cases, 2(3), 53–60.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Kalalau Timeshare/Vacation Ownership Inc. -- Case studies; Job satisfaction -- Case studies; Consumer satisfaction -- Case studies